Pyramide de Joël Hubaut, restauration d’une œuvre mixte - Aurélie Martin (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Pyramide is one element of the installation art named Le Triangle de Gertrude dans la Voie Lactee. In 1983, the french national contemporary art fund - FNAC bought Pyramide, wich is now considered by the institution as a sculpture. It was very deteriorated because of the use of multiple constitutive materials. Some of them were incompatible. Multiplicity of materials implied to identify them, to elaborate a sensibility test protocal and to determine wich elements (materials and immaterials) had to be treated during this restoration.